Historical Legacies and Urbanization: Evidence from Chinese Concessions - Gan Jin; Günther Schulze (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper shows how colonial powers permanently shaped the pattern of Chinese cities through the establishment of Concessions - foreign enclaves within Chinese cities. Based on a sample of 130 city districts within 10 Chinese cities, we find that districts with Concessions have higher land value and housing price today. Moreover, Concessions run by countries with British legal origin out-perform the ones run by countries with French legal origin, whereas Japanese Concessions barely contribute to Chinese urbanization. Finally, we show that better institutions in Concessions facilitated the emergence of modern road networks in Chinese cities that persist today and contribute to Chinese urbanization.
Keywords: N95; O18; O43; P48; R5; 330; Institutions; Urban pattern; Economic development; Persistence; Land use; Housing; China